2002
DOI: 10.1023/a:1020655724911
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Genistein is often used as an inhibitor of tyrosine kinases. A less studied side effect of genistein is an inhibition of cyclic AMP-phosphodiesterase (cAMP-PDE) activity resulting in increased cAMP accumulation. The effect of genistein on intracellular cAMP-levels, basal and forskolin-induced, was studied in A549 human airway epithelial cells and compared with the unspecific PDE inhibitor, isobutylmethylxanthine (IBMX). It was shown that genistein (50 microM) increased basal cAMP and potentiated forskolin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 179 publications
(208 reference statements)
0
2
0
Order By: Relevance
“…PDEs are negative regulators of intracellular cyclic nucleotide generation; dysregulated PDE expression has been observed in lung [4] and brain [5] tumor tissues, and found to be associated with unfavorable clinical prognosis. Notably, previous studies have shown that inhibition of PDEs leads to inhibition of cell proliferation or induction of apoptosis in NSCLC cells [6], glioblastoma stem-like cells [7], and diffuse large B-cell lymphoma cells [8]. These findings suggest that PDEs may be considered as an effective therapeutic target for NSCLC treatment.…”
Section: Introductionmentioning
confidence: 85%
“…PDEs are negative regulators of intracellular cyclic nucleotide generation; dysregulated PDE expression has been observed in lung [4] and brain [5] tumor tissues, and found to be associated with unfavorable clinical prognosis. Notably, previous studies have shown that inhibition of PDEs leads to inhibition of cell proliferation or induction of apoptosis in NSCLC cells [6], glioblastoma stem-like cells [7], and diffuse large B-cell lymphoma cells [8]. These findings suggest that PDEs may be considered as an effective therapeutic target for NSCLC treatment.…”
Section: Introductionmentioning
confidence: 85%
“…(3B) and regulates gene expression in vascular ECs [101]. Genistein also has been shown to increase intracellular accumulation of cAMP in other tissues including pancreatic beta-cells [135], airway epithelial cells [136] and cardiomyocytes [137], suggesting that genistein possibly influences a wide spectrum of cAMP-mediated biological activities.…”
Section: Genistein No and The Camp Signalingmentioning
confidence: 99%